PENGARUH KEMAMPUAN, KEPRIBADIAN, DAN SIKAP TERHADAP SEMANGAT KERJA DAN KINERJA KARYAWAN PT. PRIMA RINTIS KOTA PEKANBARU - Saputra, Rendra Aji; Indarti, Sri; Garnasih, Raden Lestari (Jurnal Tepak Manajemen Bisnis, 2019)
This research was conducted at PT. Prima Rintis which is located on Jl.Soekarno Hatta 235, Pekanbaru. The purpose of this study was to find out andanalyze the influence of abilities, personality, and attitudes towards the morale ofPT. Prima Rintis Kota Pekanbaru, to find out and analyze the influence ofabilities, personality, and attitudes towards the performance of PT. Prima RintisPekanbaru City, and to know and analyze the influence of abilities, personality,and attitudes towards performance through the morale of employees of PT. PrimaRintis Pekanbaru City. Where in this study the population is all employees at PT.Prima Rintis. In conducting this study the authors took samples from a populationof 95 employees and processed data using path analysis methods with the SPSSprogram. Based on the discussion and results of the study, several conclusionscan be made such as the following: Ability has a dominant and strong influenceon the morale of PT. Prima Rintis Pekanbaru City, Personality has a dominantand strong influence on employee morale, Work attitude has a dominant andstrong influence on employee morale, Ability does not have a significant effect onemployee performance, Personality has a dominant and strong influence onemployee performance, Attitude work has a dominant and strong influence onemployee performance. The spirit of work has a dominant and strong influence onemployee performance. The spirit of work is not able to mediate the effect ofability on employee performance. The spirit of work is able to mediate theinfluence of personality on employee performance, and work spirit can mediate influence work attitude towards employee performance